Altered Effective Connectivity in the Default Network of the Brains of First-Episode, Drug-Naïve Schizophrenia Patients With Auditory Verbal Hallucinations - Zhao, Zhiyong; Li, Xuzhou; Feng, Guoxun; Shen, Zhe; Li, Shangda; Xu, Yi; Huang, Manli; Xu, Dongrong (Frontiers in Human Neuroscience, 2018)
Although the default mode network (DMN) is knowing to be abnormal in schizophrenia patients with auditory verbal hallucinations (AVHs), it is still unclear whether the AVHs occurred to schizophrenia are associated with certain information flow in the DMN. The present study collected resting-state functional magnetic resonance imaging data from 28 first-episode, drug-naïve schizophrenia patients with AVHs, 20 schizophrenia patients without AVHs and 38 healthy controls. We used Granger Causality Analysis (GCA) to examine effective connectivity of two hub regions (posterior cingulate cortex (PCC) and anteromedial prefrontal cortex (aMPFC)) within the DMN. We used two-sample t-tests to compare the difference in effective connectivity between the two patient groups and used Spearman correlation analysis to characterize the relationship between imaging findings and clinical assessments. GCA revealed that compared with non-AVHs group, effective connectivity decreased from aMPFC to the left inferior temporal gyrus (ITG) and from PCC to the left cerebellum posterior lobe, inferior temporal gyrus and right middle frontal gyrus in schizophrenia patients with AVHs. We also found significant correlations between clinical assessments and the mean strengths of connectivity from aMPFC to left ITG and from PCC to left ITG. Moreover, receiver operating characteristic analysis revealed that the effective connectivities above-mentioned had a diagnostic value for distinguishing schizophrenia patients with AVHs from non-AVHs patients. These findings suggest that AVHs in schizophrenia patients may be associated with the aberrant information flows of DMN and left ITG may probably serve as a potential biomarker for the neural mechanisms underlying AVHs in schizophrenia patients.